Error estimates of expanded mixed methods for optimal control problems governed by hyperbolic integro‐differential equations. Issue 5 (14th February 2013) - Hou, Tianliang
Abstract In this article, we investigate the L∞(L2) ‐error estimates of the semidiscrete expanded mixed finite element methods for quadratic optimal control problems governed by hyperbolic integrodifferential equations. The state and the costate are discretized by the order k Raviart‐Thomas mixed finite element spaces, and the control is approximated by piecewise polynomials of order k(k ≥ 0). We derive error estimates for both the state and the control approximation. Numerical experiments are presented to test the theoretical results. © 2013 Wiley Periodicals, Inc. Numer Methods Partial Differential Eq, 2013